Энергетические аспекты топологоэксергетического метода описания физико-технологических систем (ФТС). Часть 2 - Тучин, В. Т.; Долгополов, И. С.; Братута, Эдуард Георгиевич; Тучина, У. Н. (НТУ "ХПИ", 2005)
The power aspects of a topologoexergycal method are esteemed. This method are developed for the analysis of saving energy in physico-technological systems by the writers. The evidence of applicability of the Tellegen's theorem is adduced for topologoexergycal frames of communication. The consequents from this theorem are reviewed that having practical value at the analysis of efficiency of power frame FTS. In the second part of article the examples of calculation of the FTS are given with using of the quasiexergical power theorem.
Keywords: квазиэксергетическая мощность; метод описания ФТС